Progress on impoverishing health spending in 122 countries: a retrospective observational study - Wagstaff, Adam; Flores, Gabriela; Smitz, Marc-François; Hsu, Justine; Chepynoga, Kateryna; Eozenou, Patrick (The Lancet global health, 2018)
The goal of universal health coverage (UHC) requires that families who get needed health care do not suffer financial hardship as a result. This can be measured by instances of impoverishment, when a household's consumption including out-of-pocket spending on health is more than the poverty line but its consumption, excluding out-of-pocket spending, is less than the poverty line. This links UHC directly to the policy goal of reducing poverty. We measure the incidence and depth of impoverishment as the difference in the poverty head count and poverty gap with and without out-of-pocket spending included in household total consumption. We use three poverty lines: the US$1·90 per day and $3·10 per day international poverty lines and a relative poverty line of 50% of median consumption per capita. We estimate impoverishment in 122 countries using 516 surveys between 1984 and 2015. We estimate the global incidence of impoverishment due to out-of-pocket payments by aggregating up from each country, using a survey for the year in question when available, and interpolation and model-based estimates otherwise. We do not derive global estimates to measure the depth of impoverishment but focus on the median depth for the 122 countries in our sample, accounting for 90% of the world's population. We find impoverishment due to out-of-pocket spending even in countries where the entire population is officially covered by a health insurance scheme or by national or subnational health services. Incidence is negatively correlated with the share of total health spending channelled through social security funds and other government agencies. Across countries, the population-weighted median annual rate of change of impoverishment is negative at the $1·90 per day poverty line but positive at the $3·10 per day and relative poverty lines. We estimate that at the $1·90 per day poverty line, the worldwide incidence of impoverishment decreased between 2000 and 2010, from 131 million people (2·1% of the world's population) to 97 million people (1·4%). The population-weighted median of the poverty gap increase attributable to out-of-pocket health expenditures among the 122 countries in our sample are ¢1·22 per capita at the $1·90 per day poverty line and ¢3·74 per capita at the $3·10 per day poverty line. In all countries, out-of-pocket spending can be both catastrophic and impoverishing at all income levels, but this partly depends on the choice of the poverty line. Out-of-pocket spending on health can add to the poverty head count and the depth of poverty by diverting household spending from non-health budget items. The scale of such impoverishment varies between countries and depends on the poverty line but might in some low-income countries account for as much as four percentage points of the poverty head count. Increasing the share of total health expenditure that is prepaid, especially through taxes and mandatory contributions, can help reduce impoverishment. Rockefeller Foundation, Ministry of Health of Japan, and UK Department for International Development.